Migrant Ecologies Environmental Histories of the Pacific World - Beattie, James; Jones, Ryan Tucker (2023)
Migrant Ecologies: Environmental Histories of the Pacific World is the first volume explicitly dedicated to the environmental history of Earth's largest ocean. Covering nearly one-third of the planet, the Pacific Ocean is remarkable for its diverse human and non-human inhabitants, their astounding long-distance migrations over time, and their profound influences on other parts of the world. This book creates an understanding of the past, present, and futures of the lands, seas, peoples, practices, microbes, animals, plants, and other natural forces that shape the Pacific. It effectively argues for the existence of an interconnected Pacific World environmental history, as well as for the Pacific Ocean as a necessary framework for understanding that history. The fifteen chapters in this comprehensive collection, written by leading experts from across the globe, span a vast array of topics, from disease ecology and coffee cultivation to nuclear testing and whaling practices. They explore regions stretching from the Tuamotu Archipelago in the south Pacific to the Kamchatka Peninsula in the far north, resisting the depiction of the Pacific as isolated and uninhabited. What unites these diverse contributions is a concern for how the people, places, and non-human beings of the Pacific World have been shaped by, and have in turn modified, their oceanic realm. Building on a recent renaissance in Pacific history, these chapters make a powerful argument for the importance of the Pacific World as a coherent unit of analysis and a valuable lens through which to examine past, ongoing, and emerging environmental issues. By showcasing surprising and innovative perspectives on the environmental histories of the peoples and ecosystems in and around the Pacific Ocean, this work adds to current conversations and debates about the Pacific World and offers myriad opportunities for further discussions, both inside and outside of the classroom.